Correlations of Vitamin D Forms and Vitamin K Forms Within Four Human Brain Regions: The Memory and Aging Project (MAP) (P14-025-19). (13th June 2019) - Patterson, Will; Booth, Sarah; Dolnikowski, Gregory; Dawson-Hughes, Bess; Morris, Martha; Holland, Thomas; Fu, Xueyan
Abstract: Objectives: Vitamins D and K are detected in the human brain, but the associations among the forms of vitamin D and vitamin K within brain region is unclear. The objective of this study is to evaluate the correlations of vitamin D forms and vitamin K forms within four regions of the human brain. Methods: Post-mortem brain samples were obtained from 130 participants in the Rush Memory and Aging Project, a prospective cohort of community-dwelling adults from Chicago, IL (age range 78–86 y; 81% Female). Vitamin D [D3, 25(OH)D and 1, 25(OH)2D] and vitamin K (phylloquinone and MK4) concentrations were measured by LC/MS/MS and HPLC, respectively, in the following regions: middle frontal cortex (MF) and middle temporal cortex (MT) [two key memory regions affected by Alzheimer's Disease (AD)], cerebellum, (CR, which is unaffected by AD), and the anterior watershed white matter (AWS, associated with vascular disease). The correlations among nutrient forms within each region were calculated using Spearman rank order correlation coefficients. Statistical significance was set at P  < 0.001. Results: Within the MT region, D3, 25(OH)D, and 1, 25(OH)2D were all positively correlated with one another (all Spearman r  ≥ 0.35, P  < 0.0001). Within the MF, AWS, and CR regions, 25(OH)D and D3 were positively correlated (Spearman r  = 0.62, 0.61 and 0.46 respectively, all P  < 0.0001), but 1, 25(OH)2D was not significantly correlated with D3 or 25(OH)D (all Spearman r  ≤ 0.21, P  ≥ 0.02). No statistically significant correlations were detected between phylloquinone and MK4 (all Spearman r  ≤ 0.17, P  ≥ 0.05) in any region. Conclusions: Vitamin D forms were significantly positively correlated within the four regions studied, but vitamin K forms were not. These data provide insight into a potential role for vitamin D and vitamin K in AD and dementia that merits future study. Funding Sources: Supported by the National Institute of Aging.